Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1477-3155-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 coated nanofiber scaffolds for the repair of damaged cardiac tissue

Abstract: After a cardiac event, proper treatment and care of the damaged tissue is crucial in restoring optimal cardiac function and preventing future cardiac events. Recently, thymosin β4 has been found to play a vital role in cardiac cell health and development by regulating angiogenesis, inflammatory responses, and wound healing. We proposed that defined poly(ϵ-caprolactone) (PCL) nanoscaffolds coated with thymosin β4 could efficiently differentiate murine-derived cardiomyocytes into functioning cardiac tissue. PCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Cell therapies also have potential in cardiovascular medicine and, indeed, transplant of modified embryonic stem cells which over-express Tβ4 have been shown to have benefit in a rat model of myocardial infarction [ 22 ]. Additionally, Tβ4 has been used to facilitate the production of cardiac patches designed to replace damaged tissue following myocardial infarction [ 23 ]. Knowledge of which cells Tβ4 is important to during normal development will help to refine and enhance such cell-based therapies for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Cell therapies also have potential in cardiovascular medicine and, indeed, transplant of modified embryonic stem cells which over-express Tβ4 have been shown to have benefit in a rat model of myocardial infarction [ 22 ]. Additionally, Tβ4 has been used to facilitate the production of cardiac patches designed to replace damaged tissue following myocardial infarction [ 23 ]. Knowledge of which cells Tβ4 is important to during normal development will help to refine and enhance such cell-based therapies for clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, electrospinning has attracted numerous interests as a simple and effective method [ 3 ]. Many studies have reported that artificial scaffolds composed of biocompatible polymers and various biomaterials can be manufactured by electrospinning [ 3 - 8 ]. In particular, electrospun matrices, composed of various polymers, including polyesterurethane, poly(ε-caprolactone) and poly(hydroxybutyrate), coated with proteins or not, have been designed as potential artificial scaffolds for skeletal muscle regeneration [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the reduction in the size of MI and fibrosis was reported with an increase in scar thickness. PCL-based nanoscaffolds with thymosin β4 coating functionalized with murine-derived cardiomyocytes to improve cardiac functions were also reported [114].…”
Section: Nanofibersmentioning
confidence: 99%